THE EFFECTIVENESS OF GOOD GOVERNANCE INDICATORS IN ALGERIA - Khalil Bouhelais , Dr. Mohamed (The journal of contemporary issues in business and government, 2023)
This research paper aims to assess the governance status in Algeria through a descriptive analysis of the Worldwide Governance Indicators (WGI). These indicators encompass six sub-indices, each assessing a dimension of good governance, including anti-corruption efforts, government effectiveness, political stability and absence of violence, regulatory quality, rule of law, and voice and accountability. Despite the Algerian government's efforts to implement various measures and regulations aimed at bolstering the principles of good governance, the findings of the study indicate that Algeria's performance across these indicators remains notably deficient. This deficit underscores persistent challenges and shortcomings within Algeria's governance framework, highlighting the need for continued reforms and concerted efforts to address underlying issues and enhance governance practices in the country.